Towards a novel and efficient method to determine the failure energy of rockfall chain-link meshes. (March 2020) - Tahmasbi, S.; Giacomini, A.; Wendeler, C.; Buzzi, O.
Abstract: Quantifying the maximum energy that a rockfall mesh, or a full system, can dissipate before failing is an inherent part of characterizing its dynamic response. Finding the failure energy is often done experimentally, which can be very time consuming and quite expensive. This paper proposes a novel approach, based not only on the kinetic energy at impact but also on the block residual velocity. Using this additional information enables one to efficiently analyse the drop test results and estimate the failure energy from two tests only, one in the rebound range and one in the perforation range, with less than 4% of error.